The Whale and the Region: Orca Capture and Environmentalism in the New Pacific Northwest - Colby, Jason (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2013)
Although the orca is today widely recognized as a cultural and ecological icon of the Pacific Northwest, historians have ignored the impact of killer whale capture on the development of the region’s environmental values and identity. Between 1964 and 1976, the waters in southern British Columbia and Washington State were the world’s principal source of captive killer whales. The display of orcas by the region’s aquariums transformed human perceptions of this marine predator, and soon aquariums around the world were placing orders for Pacific Northwest killer whales. Yet the expanding capture and export of orcas in the late 1960s and early 1970s raised troubling ecological and moral questions for the region’s human residents. In the context of shifting attitudes toward cetaceans and rising environmental awareness throughout North America, Pacific Northwesters on both sides of the border increasingly viewed orcas as symbols of their region’s shared ecological concerns. The transnational nature of the region’s killer whale pods helped spur not only ecological reflection but also transborder cooperation among activists, scientists, and government officials to study and eventually protect the species. In the process, the shifting human relations with orcas helped redefine the Pacific Northwest.